The Rôle of Theory in Translator Training: Some Observations about Syllabus Design - Shuttleworth, Mark (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
Abstract“With doubts about the usefulness of translation theory never far from many people's minds, this paper seeks to consider exactly what it is that we are trying to achieve by including a theoretical component in translator training programmes. Within this context the paper specifically examines the possibilities of generic theory courses — in which students who are working with different language pairs and who probably have only a single language in common are all taught together — as opposed to a more language-specific approach. In order to attain the relevance that they purportedly so often lack, such courses need to set a fairly broad agenda for themselves, seeking if possible to address the type of questions likely to be uppermost in students' minds, expose students to a range of differing opinions on controversial issues, provide an alternative to standard dichotomies, encourage participants to arrive at their own strategies for solving translation problems, prepare students for work within the translation industry and demonstrate that translation is not an activity which is completely ad hoc and subjective. The paper furthermore suggests that every effort should be made to harmonise the formal theory component with everything else that goes on in the programme, so that theory is seen to be relevant to practice. Within this broader perspective one of the main purposes of this training component should therefore be to enable students to develop their own personal, internalised theory which will inform their developing performance as professional translators.”